Influence of different berry thermal treatment conditions, grape anthocyanin profile, and skin hardness on the extraction of anthocyanin compounds in the colored grape juice production. (November 2015) - Lambri, Milena; Torchio, Fabrizio; Colangelo, Donato; Río Segade, Susana; Giacosa, Simone; De Faveri, Dante Marco; Gerbi, Vincenzo; Rolle, Luca
Abstract: To reduce the production surplus of grapes in the wine industry and, at the same time, to meet the growing demand of nutritious foods by health-conscious consumers, alternative processes with better sustainability are needed. In the production of colored grape juices for direct consumption, the application of heat on crushed grapes is a possible technology to increase extraction of anthocyanins and other phenolic compounds. To achieve this aim, three different thermal treatments were performed on crushed grapes of two different red varieties with peonidin or malvidin prevalence in the anthocyanin profile. Qualitative and quantitative differences in the chemical composition and color characteristics of the juices were evaluated to pinpoint the time–temperature combination that allowed the highest extraction of anthocyanins. Furthermore, the modification of skin mechanical properties during thermal treatment and impact of the peonidin/malvidin ratio on juice color were investigated. The use of high temperatures for short times was the most profitable time–temperature combination based on the extraction efficacy, color stability and energetic requirements. Highlights: Three thermal treatments were applied on crushed grapes for colored juice production. Chemical composition and color characteristics of the grape juices were evaluated. The variety effect was evaluated using winegrapes with different anthocyanin profiles. Relationships of skin mechanical properties with anthocyanin extraction were studied. High temperature for short time was the best combination for the anthocyanin release.